OKULTISME KEJAWEN - Chaliya Elisabet T - (STT Bethel The Way, 2021)
The purpose of this study is to describe the Kejawen occult, which includes the sources of the occult, the teachings, practices that are still practiced to this day along with the dangers in the lives of Javanese people and believers. This research was conducted using a descriptive qualitative method aimed at describing, describing facts, phenomena regarding the Occult Kejawen in Javanese society. The results showed that Kejawen was practiced by ancestors in Java who believed in the existence of spirit or natural forces and lived side by side with them. This Kejawen is passed down to the next generation and is preserved as a hereditary tradition in Javanese society, consciously or unconsciously starting when they are still in the womb. Kejawen itself is a combination or mixture of beliefs and rituals of formal religions with worship of nature. The researcher concludes that the occult is still practiced in people's lives in Java today, namely kejawen, which is binding starting from pregnancy, birth, marriage, spirituality, life, to death. The danger of practicing the occult is that the perpetrator will experience some nervous breakdowns, be physically tormented, depressed and even die spiritually. The Bible records the characteristics of occult actors, namely their faith is twisted, full of deceit, enemies of the truth, always turning God's way (Acts 13:10) full of all kinds of tyranny, greed, corruption, envy, murder, strife, wickedness (Rm. 1:29). Keywords: Occult, Kejawen